THIRD MOLAR IMPACTION AND AGENESIS: A REVIEW - MAMUN KHAN SUJON; MOHAMMAD KHURSHEED ALAM; HAMID H ENEZEI; SHAIFULIZAN ABDUL RAHMAN (International Journal of Pharma and Bio Sciences, 2015)
In clinical dentistry third molar have great prevalence. These teeth are commonly found to be impacted and sometimes it’s may absent in the oral cavity. The aim of the study was to evaluate the prevalence of different pattern, angulation of third molar impaction and third molar agenesis between different ages of different races. Several electronic databases such as Google Scholar, PubMed, Web of Science and Science Direct were systematically searched for studies published until March 2015. The mandibular impactions were found to be more prevalent as compared to maxillary impaction. However the agenesis of third molar does not depend on age, sex and race.